1995
DOI: 10.1172/jci117705
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary cholesterol and fat saturation on plasma lipoproteins in an ethnically diverse population of healthy young men.

Abstract: The individual effects of dietary cholesterol and fat saturation on plasma lipoprotein concentrations were determined in an ethnically diverse population of normolipidemic young men (52 Caucasian, 32 non-Caucasian). The experimental diets contained -200 or 600 mg/d of cholesterol, 36-38% of calories as fat, and high or low proportions of saturated and polyunsaturated fat (polyunsaturated/saturated fat ratio -0.8 vs 0.3). At the lower cholesterol intake, the high saturated fat diet had only a modest effect on L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0
5

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(58 citation statements)
references
References 35 publications
1
52
0
5
Order By: Relevance
“…However, according to Dietschy (1998) recent important observations have been made in relation to the quantitative effect of dietary fatty acids (FA) on TC that seem to be dependent on the cholesterol consumption, because the simultaneous consumption of either SFA or unsaturated fatty acid will raise or lower, respectively, the LDL-C concentration achieved by the dietary cholesterol. Data of Spady & Dietschy (1998) in hamsters and Fielding et al (1995) in humans have also indicated that the effect of SFA is quantitatively much greater when larger amounts of cholesterol are added to the diet. Moreover, practically no effect on the LDL-C concentrations has been found when little cholesterol was present in diet.…”
Section: Introductionmentioning
confidence: 91%
“…However, according to Dietschy (1998) recent important observations have been made in relation to the quantitative effect of dietary fatty acids (FA) on TC that seem to be dependent on the cholesterol consumption, because the simultaneous consumption of either SFA or unsaturated fatty acid will raise or lower, respectively, the LDL-C concentration achieved by the dietary cholesterol. Data of Spady & Dietschy (1998) in hamsters and Fielding et al (1995) in humans have also indicated that the effect of SFA is quantitatively much greater when larger amounts of cholesterol are added to the diet. Moreover, practically no effect on the LDL-C concentrations has been found when little cholesterol was present in diet.…”
Section: Introductionmentioning
confidence: 91%
“…In a study of normolipidemic young men (52 Caucasian and 32 non-Caucasian), Fielding et al (24) compared the effects of diets high or low in saturated and polyunsaturated fat (polyunsaturated/ saturated fat ratio 0.8 versus 0.3). The study also compared diets high versus low in cholesterol (200 mg versus 600 mg).…”
Section: It Is Not All About Fasting Cholesterol Levelsmentioning
confidence: 99%
“…Fasting cholesterol levels are determined mainly by heredity, insulin resistance [22,23] , obesity, and factors other than what was consumed the previous day. The widespread emphasis on saturated fat as the main determinant of fasting levels of LDL is also misplaced: dietary cholesterol is permissive of the effects of saturated fat on fasting lipid levels [24] . Saturated fat has a much greater effect on fasting LDL when it is consumed with cholesterol [24] ; this has been called the "bacon and egg" effect [25] .…”
Section: Diet Is About the Post-prandial Statementioning
confidence: 99%
“…The widespread emphasis on saturated fat as the main determinant of fasting levels of LDL is also misplaced: dietary cholesterol is permissive of the effects of saturated fat on fasting lipid levels [24] . Saturated fat has a much greater effect on fasting LDL when it is consumed with cholesterol [24] ; this has been called the "bacon and egg" effect [25] . Recent analyses suggesting that saturated fat may not be harmful were therefore overly simplistic: effects of saturated fat must be considered in relation to cholesterol intake.…”
Section: Diet Is About the Post-prandial Statementioning
confidence: 99%